2020
DOI: 10.3390/s21010218
|View full text |Cite
|
Sign up to set email alerts
|

Survivability-Enhanced Virtual Network Embedding Strategy in Virtualized Wireless Sensor Networks

Abstract: With the widespread application of wireless sensor networks (WSNs), WSN virtualization technology has received extensive attention. A key challenge in WSN virtualization is the survivable virtual network embedding (SVNE) problem which efficiently maps a virtual network on a WSN accounting for possible substrate failures. Aiming at the lack of survivability research towards physical sensor node failure in the virtualized sensor network, the SVNE problem is mathematically modeled as a mixed integer programming p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…b. Long-term Average Revenue to Cost Ratio: First, after a request is successfully deployed at time T, its revenue is defined as in (10), and its cost is defined as in (11). Where () v cpu n represents the CPU resource constraint required by the virtual node v n in the request, () v bw l represents the bandwidth resource constraint required by the virtual link v l in the request, and () v Ml represents the underlying physical path that maps the virtual link.…”
Section: Simulation Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…b. Long-term Average Revenue to Cost Ratio: First, after a request is successfully deployed at time T, its revenue is defined as in (10), and its cost is defined as in (11). Where () v cpu n represents the CPU resource constraint required by the virtual node v n in the request, () v bw l represents the bandwidth resource constraint required by the virtual link v l in the request, and () v Ml represents the underlying physical path that maps the virtual link.…”
Section: Simulation Results Analysismentioning
confidence: 99%
“…First, in the existing delay-aware research, the authors of [8][9][10] assign the delay as a resource to the underlying link, and set the algorithm optimization goal to minimize link delay resources to meet low-latency requirements slicing business request. The authors of the literature [11,12] transformed the optimization goal of minimizing the delay into the topology goal of the minimum number of hops in the path, and achieved the purpose of reducing the delay by reducing the node size and the number of transmission hops in the path. Secondly, in the current research on reliability perception, the literature [13][14][15][16][17] improves the reliability of the network by setting backup.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the primary focus of WVNE is link assignment, some research works consider node properties in wireless scenarios. In [34] the selection of nodes is based on the cost of all potential choices in the substrate network, and [35] proposes an algorithm that makes the election according to the cost of executing a task in a node that has a certain degree of failure and the deployed backup entities that may recover it.…”
Section: Related Workmentioning
confidence: 99%
“…For that purpose, virtual network embedding (VNE) techniques are used to automate this process and optimize the assignment in each setting. New algorithms must be suggested that fit the special features of constrained devices and guarantee good quality of service in smart perception networks [94]. • Privacy: Mist Computing gives the opportunity to change the present model of sharing and storing data according to privacy policies, which was established by the Cloud, i.e., gathering all information in an external centralized organization.…”
Section: Open Challengesmentioning
confidence: 99%